Sustainable Value Chain Innovation for Strengthening The Indonesian Halal Beef Industry - Mahbubi, Akhmad (Muslim Business and Economics Review, 2023)
This study aims to examine the product, process, and business model value innovation of halal beef in Indonesia. This study uses quantitative and qualitative data. Through purpose sampling, the survey involved 425 middle-class Muslim consumers, 100 beef retailers, 25 beef processors, and 100 mid-to-large-scale cattle farmers. It finds that product value innovation steer halal beef producers and suppliers should eliminate the fat content of halal beef. Suppliers should reduce their focus on the attributes of size, grade, taste, nutritional value, production origin, beef availability, packaging, shopping location, display in the shop, ease of preparation, traceability, price, and the presence of a Muslim shop owner. Instead, they should improve the attributes of newness, appearance, halal labels, texture, aroma, hygiene, and residue free. They should create online services and ensure halal certification of their stores. Meanwhile, process value innovation should take the form of beef producers eliminating aging and deboning activities. In essence, Each actor should keep doing the same activities but also take more seriously how their activities impact values and emissions. Cattle farmers should improve cattle feed management to earn higher, and beef retailers should create online services for their customers. Furthermore, business model value innovation should change relationship patterns from collaborative transactions to collaborative processes. Digital resources can be used as new distribution channels and online services. Finally, business model value innovation will shift from the red ocean to the blue ocean competition.